Antibacterial wood-plastic composite material for pallets and preparation method thereof
By adopting specific formulas and processes in the tray wood-plastic composite materials, including the use of modified antibacterial agents and plant fibers, the problems of insufficient mechanical properties, antibacterial properties and cleaning properties of the tray materials are solved, and higher mechanical properties, better antibacterial effects and more convenient cleaning properties are achieved.
Patent Information
- Application Number
- CN202410806620.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-21
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-06-21
AI Technical Summary
The existing wood-plastic composite materials for pallets have shortcomings in mechanical properties, antibacterial properties and cleaning properties, resulting in weaker mechanical properties, weaker antibacterial effects and inconvenient cleaning in logistics and transportation and daily use.
An antibacterial wood-plastic composite material for trays is used, and its formulation includes 50-150 parts of polyethylene, 20-60 parts of polypropylene, 20-80 parts of plant fiber, 0.01-2 parts of catalyst and 15-60 parts of modified antibacterial agent. The modified antibacterial agent is prepared from a modifier, a plasticizer, an initiator, a coupling agent and an antibacterial agent, and is stirred and melt-extruded through specific process steps.
Improves the mechanical properties and antibacterial properties of the tray wood-plastic composite material, making it easier to clean, extends service life and reduces the risk of bacterial growth.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wood-plastic composite materials, and in particular to an antibacterial wood-plastic composite material for a pallet and a preparation method thereof. Background Art
[0002] Pallets are widely used as a means of transporting goods in the logistics and transportation industry. They have high requirements for material durability, load-bearing capacity, and environmental protection. Although traditional wooden pallets are low-cost, they are susceptible to moisture, decay, and have a short service life; while metal pallets are durable, they are expensive and prone to rust and corrosion. Therefore, finding a pallet material that is both durable and environmentally friendly has become an urgent need in the industry.
[0003] However, wood-plastic composite materials are a new type of composite materials, which use polyethylene, polypropylene and polyvinyl chloride instead of the usual resin adhesives, and mix with more than 50% of waste plant fibers such as wood powder, rice husks, straw, etc. to form new wood materials. This material is processed by plastic processing such as extrusion, molding, injection molding, etc. to produce boards or profiles, which are mainly used in building materials, furniture, logistics packaging and other industries.
[0004] Wood plastic composite materials have many excellent properties. They have good weather resistance and corrosion resistance, and excellent processing performance. They can be sawed, drilled, planed, bonded, etc. like wood, and can also be hot pressed, extruded, and molded like plastic. This characteristic makes wood plastic composite materials have a wide range of application prospects in furniture, decorative materials and other fields.
[0005] CN113861710A discloses an antibacterial raw material powder, an antibacterial wood-plastic composite material and a preparation method thereof, wherein the antibacterial raw material powder is prepared by using plant fiber raw material powder and shell powder after high temperature calcination, and then the antibacterial wood-plastic composite material is prepared with a polymer material. The antibacterial wood-plastic composite material prepared by the method can solve the problem that wine lees are prone to produce odor, corruption, breeding bacteria and mold, and are not easy to store for a long time. However, the antibacterial components in the wine lees of the antibacterial wood-plastic composite material prepared by the method may be lost during the preparation process, or gradually degraded during the use of the composite material, resulting in a weakened antibacterial effect.
[0006] CN104893331A discloses an antibacterial wood-plastic composite material and a preparation method thereof. The method comprises preparing a chitosan-nanosilver composite antibacterial agent by compounding chitosan and nanosilver, pretreating the surface of wood fiber powder with the composite antibacterial agent, and then blending the pretreated wood fiber powder with a plastic matrix, auxiliary materials, and processing aids to obtain a wood-plastic composite material. By pretreating wood fiber powder with a chitosan-nanosilver composite antibacterial agent, the wood-plastic composite material can be significantly improved.
[0007] However, the mechanical properties of the antibacterial wood-plastic composite material prepared by this method are weak, and the prepared product is prone to breakage or scratches.
[0008] When loading food on pallets, after the logistics transportation process is completed, the pallets need to be frequently exposed to water or disinfectants for comprehensive cleaning and disinfection for the next use. Sometimes the materials used to make the pallets make it difficult to clean them, and these liquids may not be able to effectively penetrate or adhere to the surface of the pallets, thus affecting the cleaning and disinfection effects and increasing the risk of bacterial growth. Summary of the invention
[0009] In view of the above-mentioned defects of the prior art, the technical problem to be solved by the present invention is to improve the mechanical properties and antibacterial properties of the wood-plastic composite material for pallets and make the pallets easy to clean.
[0010] To achieve the above-mentioned purpose, the present invention provides an antibacterial wood-plastic composite material for pallets, which comprises the following components, by weight: 50-150 parts of polyethylene, 20-60 parts of polypropylene, 20-80 parts of plant fiber, 0.01-2 parts of catalyst and 15-60 parts of modified antibacterial agent, wherein the modified antibacterial agent is prepared from a modifier, a plasticizer, an initiator, a coupling agent and an antibacterial agent.
[0011] Preferably, the preparation method of the modified antibacterial agent comprises the following steps:
[0012] S1. Dissolve the modifier and plasticizer at 50-80° C. with stirring, add the initiator, coupling agent and antibacterial agent, heat to 100-120° C. in a nitrogen atmosphere, stir at 200-600 rpm, then cool and condense in a nitrogen atmosphere for 1-5 h, and then cool to room temperature to obtain a mixture;
[0013] S2. Wash the mixture in S1 with n-hexane for 2-5 times and dry it at 50-70° C. to obtain a modified antibacterial agent.
[0014] More preferably, the preparation method of the modified antibacterial agent comprises the following steps, in parts by weight:
[0015] S1, dissolving 10-30 parts of a modifier and 70-100 parts of a plasticizer by stirring at 50-80° C., adding 0.1-2 parts of an initiator, 1-5 parts of a coupling agent and 2-10 parts of an antibacterial agent, heating to 100-120° C. in a nitrogen atmosphere, stirring at 200-600 rpm, then cooling and condensing in a nitrogen atmosphere for 1-5 hours, and then cooling to room temperature to obtain a mixture;
[0016] S2. Wash the mixture in S1 with n-hexane for 2-5 times and dry it at 50-70° C. to obtain a modified antibacterial agent.
[0017] Preferably, the modifier is any one of 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester, 2,3-diphenylmaleic anhydride, phenyl maleic anhydride, and 2,3-dimethylmaleic anhydride.
[0018] Preferably, the coupling agent is any one of dodecyltrimethoxysilane, octyltrimethoxysilane, and 2-methyl-3-(triethoxysilyl)propanethiol.
[0019] Preferably, the antibacterial agent is chitosan or a chitosan derivative.
[0020] Preferably, the plasticizer is cardanol glycidyl ether.
[0021] Preferably, the plant fiber is any one or more of wood flour, rice husk, and straw.
[0022] A method for preparing an antibacterial wood-plastic composite material for a pallet comprises the following steps, measured in parts by weight:
[0023] Step 1, stirring 50-150 parts of polyethylene, 20-60 parts of polypropylene, 20-80 parts of plant fiber raw materials, 0.01-2 parts of catalysts and 15-60 parts of modified antibacterial agents at 1000-2000 rpm for 20-40 minutes to obtain a mixture;
[0024] Step 2: melt-extrude the mixture at 180-230°C.
[0025] The invention also discloses application of the antibacterial wood-plastic composite material for pallets in logistics transportation.
[0026] In this recipe, the ingredients and their functions are as follows:
[0027] Polyethylene: Polyethylene is one of the raw materials for synthesizing antibacterial wood-plastic composite materials. This is mainly because the melting temperature of polyethylene is about 106℃-130℃ and the melt viscosity range is very wide. During the preparation of antibacterial wood-plastic composite materials, wood fibers will not undergo obvious thermal degradation. The polyethylene melt and filler can be fully mixed, which is conducive to the wetting of polyethylene on the fiber and the high filling of the fiber; polyethylene resin is relatively soft, so polyethylene-based wood-plastic boards are easy to nail, drill, cut and saw, and the subsequent processing is convenient and simple, which is a very prominent advantage of building boards; in addition, polyethylene has excellent moisture absorption resistance. After soaking in water for 24 hours at room temperature, the moisture absorption is less than 0.02%, and it has excellent corrosion resistance, insulation and chemical resistance. Therefore, polyethylene has very obvious advantages as the matrix resin of antibacterial wood-plastic composite materials. At the same time, polyethylene has a certain viscosity and can form a good interface with plant fiber raw materials, polypropylene and other components to improve the overall performance of the composite material.
[0028] Polypropylene: Like polyethylene, it is one of the raw materials for synthesizing antibacterial wood-plastic composites. Polypropylene is a thermoplastic with good mechanical strength and toughness. When used in combination with polyethylene, it can enhance the overall mechanical properties of the composite, including tensile strength, impact resistance and abrasion resistance. This is essential for the durability of load-bearing items such as pallets. In addition, polypropylene has good fluidity in the molten state and is easy to mix evenly with other components such as polyethylene and plant fiber raw materials. This fluidity helps to form a uniform composite material during the melt extrusion process, reducing internal defects and poor structure.
[0029] Plant fiber: Plant fibers, such as wood powder, rice husks, straw, etc., have high fiber strength and stiffness. By combining these plant fibers with plastic substrates (such as polyethylene and polypropylene), the mechanical strength of the composite material, such as tensile strength, compressive strength and flexural strength, can be effectively improved. At the same time, plant fibers such as wood powder are mainly composed of cellulose, and the cellulose molecules contain a large number of hydroxyl and hydroxymethyl functional groups, which can be cross-linked with the anhydride functional groups in the modifier, so that the wood powder can be quickly and evenly dispersed in polyethylene and polypropylene materials.
[0030] Catalyst: The side chain of the plasticizer has an unsaturation of 0-3 and has the properties of olefins. It can carry out chemical reactions such as catalytic hydrogenation, oxidation reaction, epoxidation reaction and addition reaction. Under the action of a catalyst or after heat treatment, the side chains can add to each other to complete the addition polymerization reaction. Under certain conditions, the plasticizer can undergo oxidative polymerization to obtain a plasticizer product with saturated side chains, which is beneficial to enhance the antioxidant properties and stability of the antibacterial wood-plastic composite material product.
[0031] Modifier: The anhydride group at one end of the modifier grafted polyolefin molecular chain can undergo esterification reaction or hydrogen bonding with the hydroxyl group on the surface of wood powder, and the polyolefin macromolecular chain at the other end can entangle or react chemically with the polyethylene and polypropylene matrix molecules, thereby enhancing the interfacial bonding force between the wood material and the matrix resin, thereby improving the comprehensive performance of the antibacterial wood-plastic composite material.
[0032] Plasticizer: The plasticizer molecular chain contains phenolic hydroxyl groups and a long carbon chain of 15 carbon atoms. The long carbon branched chain is in the meta position of the phenolic hydroxyl group, including saturated alkane and olefin structures. The unique chemical structure gives the plasticizer special chemical properties, so that cardanol not only has the chemical properties of aromatic compounds and unsaturated aliphatic hydrocarbons, but also has the characteristics of phenolic compounds. Its molecular structure retains the unsaturated long hydrocarbon chain structure of cardanol, and introduces epoxy groups with benzene rings, which has the characteristics of low viscosity, good flexibility, stable properties, and good heat resistance. The anhydride functional groups of plasticizers and modifiers can react with each other. Using plasticizer cardanol and its derivatives as plasticizers in antibacterial wood-plastic composites can effectively improve the compatibility, heat resistance, weather resistance and other properties of antibacterial wood-plastic composites.
[0033] Initiator: The initiator decomposes under heating conditions to produce free radicals, which can initiate the breakage and recombination of polymer chains such as polyethylene and polypropylene, thereby achieving polymerization or cross-linking of the material.
[0034] Coupling agent: Coupling agent is a substance with an amphoteric chemical structure. The group at one end of the molecule can form a chemical bond with the hydroxyl group on the surface of the wood powder, and the group at the other end can react chemically or physically entangle with the plastic matrix, thereby improving the interfacial bonding force between the wood powder and the polypropylene and polyethylene resins, and improving the mechanical properties and mechanical properties of the antibacterial wood-plastic composite material.
[0035] Antimicrobial agent: As chitosan or chitosan derivatives, antimicrobial agents contain hydroxyl functional groups that can be cross-linked with the anhydride functional groups of the modifier and the coupling agent, which is beneficial to improve the degree of polymer cross-linking and increase the mechanical properties of the antimicrobial wood-plastic composite material. At the same time, the addition of antimicrobial agents is beneficial to utilize the properties of chitosan itself and achieve good antimicrobial effects.
[0036] n-Hexane: In the preparation process of modified antimicrobial agents, after a series of chemical reactions between modifiers, plasticizers, initiators, coupling agents and antimicrobial agents, trace amounts of unreacted substances or by-products may be produced. n-Hexane, as an organic solvent, can effectively dissolve and clean these unreacted substances and impurities, thus making the modified antimicrobial agent purer.
[0037] Since the side chain of cardanol contains single double bonds, double conjugated double bonds and triple conjugated double bonds, there are more double bonds and allylic protons, which are easily initiated by initiators to generate active free radicals and chemical reactions. Because the plasticizer is a cardanol derivative in which the phenolic hydroxyl group is replaced by a condensed epoxy group, its chemical structure is very similar to that of cardanol, and it is also easy to react chemically on the unsaturated side chain. Therefore, cardanol derivatives are selected as plasticizers. Modifiers, as diene-philic components, are easy to react chemically with olefins. The chemical reaction points of modifiers and plasticizers occur preferentially on the carbon side chain, but the reaction products depend on the reaction conditions. When at high temperatures such as 160-180°C and without catalysts or initiators, the modifiers are easy to react with the conjugated diene components in the long chain structure of the cardanol side chain to generate cyclohexene cyclic compounds on the side chain, and the modifiers are grafted onto the cardanol carbon side chain to generate multifunctional compounds. Therefore, using modifiers and plasticizers as compatibilizers and mixing them with materials such as wood powder can increase the solubility of wood powder in the polyolefin matrix.
[0038] Beneficial effects of the present invention:
[0039] Compared with the existing technology, the compatibilizer is prepared by cross-linking the special structure of the plasticizer with the anhydride functional group in the modifier, and the coupling agent is used to react with the hydroxyl functional group in the plant fiber raw material. The two cooperate synergistically to increase the uniform dispersion effect and mechanical properties of the plant fiber raw material in the polyolefin, and increase the hydrophilic effect of the polymer; at the same time, the hydroxyl functional group in the antibacterial agent is used to react with the plasticizer anhydride to increase the antibacterial effect of the composite material. DETAILED DESCRIPTION
[0040] Parameters for specific chemical substances used, sources.
[0041] 3-Furancarboxylic acid, 2,5-dihydro-2,5-dioxo-, ethyl ester, CAS No.: 66311-39-5.
[0042] 2,3-Diphenylmaleic anhydride, CAS number: 4808-48-4.
[0043] Phenyl maleic anhydride, CAS number: 36122-35-7.
[0044] 2,3-Dimethylmaleic anhydride, CAS number: 766-39-2.
[0045] Dodecyltrimethoxysilane, CAS number: 3069-21-4.
[0046] Octyltrimethoxysilane, CAS number: 3069-40-7.
[0047] 2-Methyl-3-(triethoxysilyl)propanethiol, CAS number: 17980-28-8.
[0048] Cardanol glycidyl ether, CAS number: 171263-25-5.
[0049] Polyethylene, brand: 62N07, Yuyao Caijia Plastic Chemical Co., Ltd.
[0050] Polypropylene, brand: F780R, Shanghai Qiaowei Chemical Technology Co., Ltd.
[0051] Carboxymethyl chitosan, product number: xyh001, Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd.
[0052] Pseudomonas aeruginosa, Pseudomonas aeruginosa , CGMCC.1.15148, China General Microbiological Culture Collection Center.
[0053] Poplar wood powder, 100 mesh.
[0054] Example 1
[0055] A method for preparing an antibacterial wood-plastic composite material for a pallet comprises the following steps:
[0056] Step 1: put 100 kg of polyethylene, 50 kg of polypropylene, 30 kg of poplar wood powder, 0.5 kg of cobalt naphthenate and 20 kg of modified antibacterial agent into a high-speed mixer and stir at 2000 rpm for 30 min to obtain a mixture;
[0057] Step 2: Put the mixed material into a twin-screw extruder, melt extrude, shape and cut at 220°C and a screw speed of 250 rpm.
[0058] The preparation method of the modified antibacterial agent comprises the following steps:
[0059] S1. Add 20 g of 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester and 80 g of cardanol glycidyl ether into a three-necked flask, stir and dissolve at 65° C., add 0.5 g of azodimethylvaleronitrile, 1 g of 2-methyl-3-(triethoxysilyl)propanethiol and 5 g of carboxymethyl chitosan when the substance in the flask becomes a light red transparent viscous body, then heat to 100° C. in a nitrogen atmosphere, then stir at 500 rpm, cool and condense in a nitrogen atmosphere for 4 h, and then cool to 25° C. to obtain a mixture;
[0060] S2. Wash the mixture in S1 with 200 mL of n-hexane three times and dry it at 60° C. to obtain a modified antibacterial agent.
[0061] Example 2
[0062] The difference between Example 2 of the present application and Example 1 is that the 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester in S1 is replaced by 2,3-diphenylmaleic anhydride.
[0063] Example 3
[0064] The difference between Example 3 of the present application and Example 1 is that the 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester in S1 is replaced by phenyl maleic anhydride.
[0065] Example 4
[0066] The difference between Example 4 of the present application and Example 1 is that the 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester in S1 is replaced by 2,3-dimethylmaleic anhydride.
[0067] Example 5
[0068] The difference between Example 5 of the present application and Example 1 is that the 2-methyl-3-(triethoxysilyl)propanethiol in S1 is replaced by dodecyltrimethoxysilane.
[0069] Example 6
[0070] The difference between Example 6 of the present application and Example 1 is that the 2-methyl-3-(triethoxysilyl)propanethiol in S1 is replaced by octyltrimethoxysilane.
[0071] Comparative Example 1
[0072] The difference between this comparative example 1 and example 1 is that the 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester in S1 is replaced by maleic anhydride.
[0073] Comparative Example 2
[0074] The difference between this comparative example 2 and example 1 is that the 2-methyl-3-(triethoxysilyl)propanethiol in S1 is replaced by 3-(isomethacryloyloxy)propyltrimethoxysilane.
[0075] Comparative Example 3
[0076] The difference between Comparative Example 3 and Example 1 is that cobalt cyclopentaneate is not added in step 1.
[0077] Test Example 1
[0078] Static water contact angle test: Before the test, the surface of the sample to be tested was cleaned with deionized water and anhydrous ethanol, and dried in a vacuum oven for use. Using a contact angle meter, 5 μL of ultrapure water was added to the surface of the sample to be tested through a microinjector at 25°C, and the contact angle of the water droplet was measured within 0.5s to obtain a numerical value and an image. For each sample prepared in Examples 1-6 and Comparative Examples 1-3, the water droplet was tested at five different positions and the average value was taken. The test results are shown in Table 1:
[0079] Table 1 Contact angle test results
[0080]
[0081] Test Example 2
[0082] Antibacterial performance test:
[0083] Escherichia coli ( ATCC 8739 ), Staphylococcus aureus ( ATCC 8738P ), Pseudomonas aeruginosa ( Pseudomonas aeruginosa ) is the test strain, and the antibacterial properties of wood-plastic composite materials against the above three bacteria are determined according to GB / T 31402-2015 "Test method for antibacterial properties of plastic surfaces". The test results are shown in Table 2:
[0084] Table 2 Antibacterial performance test results
[0085]
[0086] Test Example 3
[0087] Mechanical properties test: (1) The tensile strength was tested according to GB / T 1040.2-2022 "Determination of tensile properties of plastics Part 2: Test conditions for molded and extruded plastics", and the tensile speed was 5 mm / min; (2) The impact strength was tested according to GB / T 1843-2008 "Determination of cantilever beam impact strength of plastics"; (3) The bending properties were tested according to GB / T 9341-2008 "Determination of flexural properties of plastics", and the loading speed was 2 mm / min; the test results are shown in Table 3:
[0088] Table 3 Mechanical properties test results
[0089]
[0090] By observing the test data results in Table 1, Table 2 and Table 3, it can be seen that the mechanical properties, hydrophilic properties and antibacterial effects of the pallet prepared in Example 1 are the best. The difference between Examples 1-4 and Comparative Example 1 is that different modifiers are used. The pallets prepared in Examples 1-4 and Comparative Example 1 have different effects in terms of antibacterial effects on three bacteria, hydrophilicity and mechanical properties, and the effects of Example 1 are better in all aspects. The possible reason is that compared with Examples 1-4 and Comparative Example 1, these modifiers contain anhydride functional groups that can react with plasticizers, antibacterial agents, and wood powder, and also contain carboxyl functional groups. The carboxyl functional groups can further cross-link with substances containing hydroxyl functional groups to increase the cross-linking density of the polymer. Because carboxyl functional groups are grafted on the polyethylene molecular chain by moderately oxidizing polyethylene and polypropylene, the relative molecular mass of the polymer is increased, which is beneficial to improving the mechanical properties of wood-plastic composite materials. At the same time, the carboxyl functional group can also react with the hydroxyl functional group in the wood powder and the antimicrobial agent to further increase the solubility of the wood powder in the polyolefin matrix. The wood powder is mainly composed of cellulose, hemicellulose and lignin, which contain a large number of hydroxyl components. When the solubility of the wood powder in the polyolefin is increased, the hydrophilicity of the polymer can be improved due to the large number of hydrophilic hydroxyl groups contained in the wood powder, thereby improving the hydrophilicity of the wood-plastic composite material. At the same time, due to the close cross-linking of the plasticizer and the antimicrobial agent, the dispersion effect of the antimicrobial agent in the polymer is increased, which also shows a better antimicrobial effect.
[0091] Compared with Example 1, Examples 5-6 and Comparative Example 2, the difference is that different coupling agents are used. The possible reason is that the coupling agent in Example 1 contains a thiol functional group in addition to a siloxane group, and the thiol functional group can also react with the hydroxyl functional group in the wood powder and the antibacterial agent to increase the dissolution amount of the wood powder. Similarly, the wood-plastic composite material exhibits good mechanical properties, hydrophilic effect and antibacterial effect.
[0092] Compared with Example 1 and Comparative Example 3, the difference is that a catalyst is added in Example 1. The possible reason is that the side chain of the modifier has unsaturation, and under the catalysis of cobalt cyclohexaneate, the side chains of the modifier itself can add to each other, thereby increasing the crosslinking degree of the polymer, which is beneficial to improving the mechanical properties of the polymer, while the crosslinking degree of the polymer without adding a catalyst is weaker.
Claims
1. An antibacterial wood-plastic composite material for pallets, characterized in that: The composition comprises the following components by weight: 50-150 parts of polyethylene, 20-60 parts of polypropylene, 20-80 parts of plant fiber, 0.01-2 parts of catalyst and 15-60 parts of modified antibacterial agent; The preparation method of the modified antibacterial agent comprises the following steps, measured in parts by weight: S1, dissolving 10-30 parts of a modifier and 70-100 parts of a plasticizer by stirring at 50-80° C., adding 0.1-2 parts of an initiator, 1-5 parts of a coupling agent and 2-10 parts of an antibacterial agent, heating to 100-120° C. in a nitrogen atmosphere, stirring at 200-600 rpm, then cooling and condensing in a nitrogen atmosphere for 1-5 hours, and then cooling to room temperature to obtain a mixture; S2, washing the mixture in S1 with n-hexane for 2-5 times, and drying at 50-70° C. to obtain a modified antibacterial agent; The modifier is 3-furancarboxylic acid, 2,5-dihydro-2,5-dioxo-ethyl ester; The coupling agent is any one of dodecyltrimethoxysilane, octyltrimethoxysilane and 2-methyl-3-(triethoxysilyl)propanethiol; The antibacterial agent is chitosan or a chitosan derivative; The plasticizer is cardanol glycidyl ether.
2. The antibacterial wood-plastic composite material for pallets according to claim 1, characterized in that: The plant fiber is any one or more of wood powder, rice husk and straw.
3. A method for preparing the antibacterial wood-plastic composite material for pallets according to any one of claims 1 to 2, characterized in that: The method comprises the following steps, in parts by weight: Step 1, stirring 50-150 parts of polyethylene, 20-60 parts of polypropylene, 20-80 parts of plant fiber, 0.01-2 parts of catalyst and 15-60 parts of modified antibacterial agent at 1000-2000 rpm for 20-40 minutes to obtain a mixture; Step 2: melt-extrude the mixture at 180-230°C.
4. Application of the antibacterial wood-plastic composite material for pallets as claimed in any one of claims 1 to 2 in logistics transportation.
Citation Information
Patent Citations
Antibacterial wood-plastic composite and preparation method thereof
CN104893331A
Antibacterial raw material powder, antibacterial wood-plastic composite material and preparation method of antibacterial wood-plastic composite material
CN113861710A
Wood-plastic composite material and preparation method thereof
CN103073778A
Injection molding material
CN107641242A